Character Education in the Kitab of Ta'limul Muta'allim by Shaykh Al-Zarnuji - Khoiriah Salmi; Samsurizal Samsurizal; Ahmad Sabri; Muhammad Zalnur (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2023)
The central issue in this research is that education in Indonesia tends to place more emphasis on cognitive and psychomotor aspects so that there is less implementation of affective aspects. This results in a lack of instilling character education, resulting in an identity crisis such as the erosion of attitudes of honesty and politeness, which gives rise to various problems such as student delinquency. The aim of this research is to determine the implementation of book values Ta'lim Muta'alim to develop the moral character of students through social values. The research method used is descriptive qualitative. The research results reveal the implementation of book values Ta'lim Muta'alim to develop the moral character of students through social values. Darul Ulum Islamic Boarding School prioritizes humbled and practice nature Ta'zim. Moral teachings included in the book Ta'lim Muta'allim Brought to life and realized, because the character of the students is suppressed and must be embedded in them at all times. Contained in the Kitab Ta'lim Muta'alim towards developing the character of students through exposure to national ideals. Being aware of national values ??that others should know about, saying congratulations, offering gifts, offering help, having a kind and polite attitude, and showing greater devotion to a sick friend are examples. Caring for and helping his friends. Female students are also aware of boundaries, even in their interactions with each other.